Agenda-setting e agenda institucional: um estudo da campanha eleitoral de 2004 na cidade de São Paulo - Reis, Andrea (2008)
The electoral campaign to the city hall of São Paulo in 2004 presented a historical importance, once it was the first, after the redemocratization, with a candidate to reelection. Being known about the great political and economical power that the municipal district of São Paulo has, here it comes the following subject: when the construction of a scenery of politic representation (CR-P) together with the rhetoric of the continuity, very frequent speech during a reelection campaign, do they guarantee an electoral victory? The electoral dispute of 2004 allowed that the traditional dispute between the petismo and the malufismo of last decades was substituted by the dispute between PT and PSDB . Therefore, the dispute, that was based on the person before and is based on the party now, could it be the consequence of a larger political understanding of the electorate from São Paulo? For us to understand the defeat of an administration that was being very appraised at the end of its administration, we noticed that we should analyze, besides PR-S, the person's from São Paulo electoral behavior, which was the calendar interpersonal of the electorate in 2004, the calendar-setting of the television media during the electoral year and also two main candidates' institutional calendar, for us to verify what would justify Marta Suplicy defeat. The media can alert and inform the voter about candidates' viability and also to transmit messages that influence the public opinion during the campaign. The communication means supply perspectives, they model candidates' images, as well as of the party, they help to promote the campaign themes and they differ the specific atmosphere and the area of relevance and of activity of each electoral competition. The construction of CR-P will be accompanied till the official end of the electoral campaign of 2004. It will be verified which were the preponderant constituent elements in the institutional calendar and in the media calendar